Effects of alignment of reinforcement material to the properties of Polymer Matrix Composite (PMC) - Aeyzarq Muhammad Hadzreel, Mohd Razali (2012)
This thesis investigated the effect of alignment of reinforcement material to the properties of polymer matrix composite (PMC). Tensile test and water absorption test were conducted in order to study the properties of polymer matrix composite (PMC) when the alignment of reinforcement material was varied. For this project, woven roving fiberglass was used as the fiber and unsaturated polyester resins as its matrix material. Hand layup process was used to fabricate the laminated composite. The specimens were divided into four major categories with different alignment and thickness of fiber and matrix which were 5 layers bidirectional, 5 layers multidirectional, 7 layers bidirectional, and 7 layers multidirectional. Tensile test showed that bidirectional alignment was better in term of mechanical properties compared to multidirectional alignment. The 5 layers bidirectional have a higher tensile strength compared to 5 layers multidirectional. While 7 layers bidirectional have a higher tensile strength compared to 7 layers multidirectional. The modulus of elasticity of bidirectional alignment was higher than multidirectional alignment. Bidirectional alignment was better because the external tensile load was equally distributed on all the fibers and transmitted along the axis of the fibers. Whereas in case of multidirectional alignment, fiber axes was non-parallel to load axis, resulting in off axis pulling of fibers and increased stress concentration causing the earlier failure of laminates. Water absorption test showed that multidirectional alignment absorbs more quantity of water compared to bidirectional alignment. Therefore, multidirectional alignment was not suitable for underwater application such as boat, canoe and yacht. It can be conclude that, the properties of PMC is depends on the alignment of reinforcement material.